2021
DOI: 10.4103/meajo.meajo_96_21
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of corneal abrasion perception of (primary health care physicians and emergency physicians) and its determinants in Saudi Arabia – A survey

Abstract: PURPOSE: The purpose of the study was to determine knowledge, practice, and resources available to primary care physicians to diagnose and manage corneal abrasion in Saudi Arabia. METHODS: This cross-sectional survey was held in 2017. Family physicians and emergency physicians attending an international conference were surveyed. The questions related to demography, invagination, and tools available in their institute were collected. The questionnaire on how to diagnose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…However, a study conducted locally reported a low level of knowledge and poor practice among primary care physicians in diagnosing and managing corneal abrasion. In addition, resources for diagnosing corneal abrasion are not uniform throughout Saudi Arabia, with limited availability in some centers [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, a study conducted locally reported a low level of knowledge and poor practice among primary care physicians in diagnosing and managing corneal abrasion. In addition, resources for diagnosing corneal abrasion are not uniform throughout Saudi Arabia, with limited availability in some centers [8].…”
Section: Introductionmentioning
confidence: 99%